Namen in uporabnost Digitalnega repozitorija COBISS (dCOBISS) - Petek, Miran (Organizacija znanja, 2021)
In 2020, IZUM released the first version of the COBISS Digital Repository (dCOBISS), which is an independent web app, intended for storing and managing digital content. It is available to all libraries in the COBISS system and it works by principles of shared access to publications in dCOBISS. A bibliographic record is required and it represents the basis for adding all types of digital content. Individual repository segments and other existing and foreseen functionalities are presented. Also open access analysis for Slovenian researchers will be supported by dCOBISS. In future, the dCOBISS app will be developed in compliance with trends, requirements and rapidly changing conditions in Slovenian libraries and in international library environments.
Keywords: analitika odprtega dostopa; dCOBISS; digital repositories; digitalni repozitoriji; discovery tools; open access analytics; OpenAIRE; orodja za odkrivanje podatkov